Glycation of the amyloid β-protein by a nicotine metabolite: A fortuitous chemical dynamic between smoking and Alzheimer's disease - Dickerson, Tobin J. (National Academy of Sciences, 2003)
The origin of Alzheimer's disease (AD) has been subjected to an intense amount of examination; however, a clear conclusion as to the nature of this crippling disease has yet to be identified. What is readily accepted is that a definitive marker of this disease is the aggregation of the amyloid β-peptide (Aβ) into neuritic plaques. The recent observation that nicotine exposure leads to delayed onset of AD has stimulated a flurry of research into the nature of this neuroprotective effect. This phenomenon has been debated, but no consensus has been reached, and although these studies have targeted nicotine, the primary alkaloid in tobacco, few studies have considered the physiological role of nicotine metabolites in disease states. Nornicotine is a major nicotine metabolite in the CNS and has been shown to participate in the aberrant glycation of proteins in vivo in a process termed nornicotine-based glycation. Herein is detailed a potentially fortuitous role of nornicotine-based glycation in relation to the pathology of AD. Specifically, nornicotine was found to covalently alter Aβ, leading to reduced peptide aggregation. Potential consequences of this reaction cascade include reduced plaque formation and/or altered clearance of the peptide, as well as attenuated toxicity of soluble Aβ aggregates. The findings described provide an alternative mechanism for nicotine neuroprotection in AD and a means for the alteration of amyloid folding based on a covalent chemical event.